Assessment of shared decision-making in community mental health care: Validation of the CollaboRATE - De las Cuevas, Carlos (Int J Clin Health Psychol, 2020)
BACKGROUND/OBJECTIVE: CollaboRATE is a 3-item self-report measure of the patient experience of shared decision-making (SDM) process. The objective of this study is to assess the psychometric properties of CollaboRATE in community mental health care. METHOD: A cross-sectional study was conducted at a Community Mental Health Center of the Canary Islands Health Service. Two hundred and fifty consecutive psychiatric outpatients were invited to participate. Of those, 191 accepted (76.40% of response rate) and completed the CollaboRATE, the Control Preferences Scale (CPS), and a form with sociodemographic and clinical variables. RESULTS: Exploratory factor analysis ratified the unidimensionality of the measure. High internal consistency was found (α Cronbach = .95, Guttman's λ = .93, and ω = .95). Strong positive correlations (p < .0001) were found between the CollaboRATE and the CPS. Only 39.80% of respondents gave the best possible score on CollaboRATE. CONCLUSIONS: This study provides evidence for the reliability and validity of the Spanish version of the CollaboRATE as a measure of SDM. The measure is quick to complete and feasible for use in outpatient mental health care. At present, a significative number of psychiatric outpatients are not involved in SDM. The use of this measure in psychiatric routine care can be a key tool in assessing and implementing SDM.